Optimum Conditions for Laccase Production by Local Isolate of Bacillus Cereus B5 - Allos, Mina M.; Hussein, Asmaa A (Al-Nahrain Journal of Science, 2018)
In this study, fifty five soil samples were collected from different places in Baghdad. Many Gram positive and negative isolates were obtained; of which 39 isolates were identified as Bacillus spp. when subjected to morphological and microscopical tests. Laccase enzyme activity was determined by quantitative methods using syringaldazine as substrate for these isolates, results indicated that 17 isolates of them are laccase producer with different specific activity ranged between (98-600) U/mg and the isolate Bacillus cereus B5 was the most efficient in the production of laccase with specific activity of 600 U/mg protein therefore, it was chosen to determine the optimum conditions for laccase production. Maximum laccase production was achieved after supplementation of the minimal salt medium (pH7) with 0.5% dextrose, 0.5% yeast extract and incubated at 35oC in shaker incubator (200 rpm) for 24h. Under these conditions, the specific activity of laccase produced in culture supernatant was sharply increased to 7000 U/mg protein.